The Multifaceted Perspectives of The Domestic Violence Case of Rizky Billar Towards Lesti Kejora: Sara Mills Critical Discourse Analysis - Yuniarsih, Yuniarsih; Rasyid, Yumna; Anwar, Miftahulkhairah (Jurnal Lingua Idea, 2023)
This paper discusses the discourse on domestic violence that befell Lesti Kejora by her husband, Rizky Billar, in the online media coverage tempo.com on 13 October 2022. This writing aims to describe feminism in the domestic violence coverage of Rizky Billar against Lesti Kejora using Sara Mills’ critical discourse analysis (CDA). The research method used is descriptive qualitative, utilizing the data analysis technique of Sara Mills’ critical discourse analysis, which emphasizes the position of the subject-object, its consequences, and the position of the reader-writer. From the analysis results, it is known that ideological and legal aspects are present through the views of legal experts on domestic violence. The discourse in the object of this research is news that shows the feminist movement in favor of women led by women's rights legal experts. However, the discourse writers tend to side with Billar, who is most likely to be released from custody. At first glance, Lesti's discourse indicates as if she was not a victim is indirectly something that marginalizes women. The author reconstructs facts into a discourse adapted to the intent and purpose. Therefore, the position of the subject-object may differ from the actor in another context.